AN EPISODE FROM THE BIOGRAPHY OF THE SUFI SHEIKH MAJD AD-DIN AL-BAGHDADI AND THE KHWAREZMIAN RULER TERKEN-HATUN - Timohin, Dmitrij Mihajlovic (History, Archeology and Ethnography of the Caucasus, 2020)
Sheikh Majd ad-Din al-Baghdadi was a prominent figure of the Kubrawiya Sufi order, and possessed not only religious authority, but also certain political influence. Amidst the rapid strengthening of Khwarezm, which by the beginning of the 13th century becomes the largest political formation in the Islamic East, Majd ad-Din al-Baghdadi gets close to Terken-Khatun, the mother of the Khwarezmshah ‘Ala’ al-Din Muhammad. Given the struggle between the court groups that unfolded in Khwarezm on the eve of the Mongol invasion, the alliance between the Sufi sheikh and Terken-Khatun was regarded a threat. As a result, the ruler of Khwarezm accused Majd ad-Din al-Baghdadi of romantic relations with the mother of Khwarezmshah, and ordered the sheikh to be executed. The contemporaries of this event considered the Mongol invasion and the fall of Khwarezm as retribution of ‘Ala’ ad-Din Muhammad for this act. The present paper does not aim to analyze the entire biography of Majd ad-Din al-Baghdadi, but pays special attention to the circumstances of his death and its description in medieval Arab-Persian historical sources. It is worth noting that a detailed account of it is mentioned in an anonymous Persian work of the 14th century, which has not yet been published fully, but only in separate fragments of its original text. In this paper we attempt not only to analyze the account of an anonymous author, but also to compare it with the information from other Arabic-Persian historical works. The existing views on this issue in the framework of Russian and foreign historiography, both in relation to the anonymous Persian historical work of the 14th century, and the information contained in it regarding the biography of the Sufi sheikh Majd ad-Din al-Baghdadi are also taken into account. The article may attract attention of our colleagues to this written monument, which undoubtedly needs to be published fully.